2018
DOI: 10.1128/jcm.01730-17
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Serogrouping of Dichelobacter nodosus Infection by Use of Direct PCR from Lesion Swabs To Support Outbreak-Specific Vaccination for Virulent Footrot in Sheep

Abstract: Virulent footrot is an economically significant disease in most sheep-rearing countries. The disease can be controlled with vaccine targeting the fimbriae of virulent strains of the essential causative agent, However, the bacterium is immunologically heterogeneous, and 10 distinct fimbrial serogroups have been identified. Ideally, in each outbreak the infecting strains would be cultured and serogrouped so that the appropriate serogroup-specific mono- or bivalent vaccine could be administered, because multivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
(80 reference statements)
1
11
1
Order By: Relevance
“…The strength of the current study is the number of flocks investigated nationally which provides the robust estimates of the prevalence of serogroups. The percentage of flocks and feet with multiple serogroups and the maximum number of serogroups per flock are higher than reported in previous UK studies 12 14 , 39 this is probably partly due to the increased sensitivity of PCR directly from DNA without culture 15 . Despite this, the number of serogroups detected in flocks is likely to be underestimated.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The strength of the current study is the number of flocks investigated nationally which provides the robust estimates of the prevalence of serogroups. The percentage of flocks and feet with multiple serogroups and the maximum number of serogroups per flock are higher than reported in previous UK studies 12 14 , 39 this is probably partly due to the increased sensitivity of PCR directly from DNA without culture 15 . Despite this, the number of serogroups detected in flocks is likely to be underestimated.…”
Section: Discussioncontrasting
confidence: 59%
“…McPherson et al 15 . Previous UK studies have used culture and slide agglutination to detect serogroups, but PCR is more sensitive 15 consequently the number of serogroups per flock is likely to be higher than previous estimates.…”
Section: Introductionmentioning
confidence: 99%
“…One major challenge in footrot elimination is the development of diagnostic tests which can discriminate reliably between target and non-target strains [1]. Regional elimination programs are usually aimed at virulent D nodosus, as large-scale elimination of benign D nodosus is not economically justifiable [25]. In Switzerland, the use of the PCR test was found to be the most economic and sensitive way to eliminate footrot in the planned nationwide control program [18].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that D. nodosus strains clustered within sheep and were transmitted between ewes over time. D. nodosus isolation is challenging and time consuming, because of the organism's fastidious and anaerobic nature and direct PCR from swab DNA is more sensitive than culture ( 15 , 22 ).…”
Section: Introductionmentioning
confidence: 99%